2019
DOI: 10.1017/s1352465819000560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Korean version of the metacognitive training program for outpatients with schizophrenia on theory of mind, positive symptoms, and interpersonal relationships

Abstract: Background:Since the significance of metacognition as the theoretical basis of a psychological intervention for schizophrenia first emerged, there have been ongoing attempts to restore or strengthen patients’ metacognitive abilities.Aim:A Korean version of the metacognitive training (MCT) program was developed, and its effects on theory of mind, positive and negative symptoms, and interpersonal relationships were examined in stable outpatients with schizophrenia.Method:A pre-test–post-test design with a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Table 1 presents the main characteristics of included studies and reports (Z. Fekete, MA, personal communication, September 2021; J.M. Lopez, PhD, personal communication, July 2021; and D. Raucher-Chéné, MD, personal communication, August 2021) and Table 2 displays participant characteristics. Table 3 and eAppendix 1 in the Supplement present the narrative review results of the 6 nonincluded studies and reports (eg, did not report ES values, secondary analyses).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the main characteristics of included studies and reports (Z. Fekete, MA, personal communication, September 2021; J.M. Lopez, PhD, personal communication, July 2021; and D. Raucher-Chéné, MD, personal communication, August 2021) and Table 2 displays participant characteristics. Table 3 and eAppendix 1 in the Supplement present the narrative review results of the 6 nonincluded studies and reports (eg, did not report ES values, secondary analyses).…”
Section: Resultsmentioning
confidence: 99%
“…This approach closely corresponds to the two component of the metacognitive framework proposed by Cella et al (2015) in order to mitigate the impact of cognitive deficits, namely, metacognitive knowledge (making the patient aware of their difficulties and of the situations in which these difficulties can have a negative impact) and metacognitive regulation (using strategies to improve performance and monitor their efficacy). Relatedly, a recent study reported improvements in ToM performance following metacognitive training (Park et al, 2020), a treatment known to improve positive symptoms in schizophrenia (Moritz et al, 2011; Moritz et al, 2013; Moritz & Woodward, 2007; van Oosterhout et al, 2016). While these approaches focus mainly on the patient, in the case of social cognition deficits, the metacognitive approach could further capitalize on the interactive nature of social interactions; raise the other person's knowledge of the patient's difficulties ( second‐person metacognitive knowledge ) and get them involved in applying strategies to mitigate the impact of the patient's difficulties ( second‐person metacognitive regulation ).…”
Section: Discussionmentioning
confidence: 99%